Socio-Cultural and Value Paradigms of Public Civil Servants in Russia - Frolova Elena V.; Ryabova Tat'yana M. (Economic and Social Changes: Facts, Trends, Forecast, 2018)
In the modern Russian society, there is a contradiction between the goals and objectives of civil service, its social relevance and applied nature, on the one hand, and the growing dissatisfaction of the population on the other hand. The article describes and analyzes the socio-cultural and value paradigms of civil servants in the Russian Federation, which define the characteristics of their activities. The authors emphasize the importance of a motivational resource such as socio-cultural and value paradigms in the process of reforming the modern institution of civil service. The research results revealed a number of problems. A significant part of the structure of life goals of civil servants is occupied by material interests; according to the respondents’ estimates, the activities they do are not related to the categories of “favorite activity”, “interesting job”. Some government employees consider “service to the Fatherland”, “useful contribution to the society and the state” as the main purpose for their professional activity. The research confirmed the hypothesis that the efficiency and effectiveness of occupational work of civil servants depends not only on motivational factors but also on life experience, moral principles, understanding of one’s role in the process of implementing the state policy and life strategy. The routine nature of work does not live up to employees’ expectations evening political activities and state administration. Bureaucratic values, lack of interaction with the external environment, authoritarian management style, and rigid subordination affect the employee’s identity and behavior. Government employees due to personal characteristics and character specifics, assessing themselves and their experience higher at the career ladder, either search for a new position themselves, a different kind of activity to meet their life strategy, or stop developing professionally. Socio-cultural and value paradigms of government employees vary according to the category and group of positions. We also confirmed the hypothesis concerning the category “experts” of leading and senior groups of positions that public service is considered by employees and citizens not as a value-regulatory complex providing interaction between the state and the society in order to meet the interests of the latter, but as a mechanism for achieving financial success